Desenvolvimento conceitual de uma maquina de ensaios mecânicos tipo pórtico - Gasparin, Daniel (2015)
It is important to prove the structural performance of a mechanical connection or structural component in a specific application in different industry sectors in order to guarantee more efficient, competitive and safe products. In this context, the work developed consisted of the idea of a mechanical steel frame testing equipment to analyze and validate metallic connection and structural components submitted to compression load path, traction and bend and static tests. For developing the idea, a project methodology consisted of four steps was used: project specification, concept project, pre-project and a detailed project, sequentially used, which were important in the organization and elaboration of the project. Yet, the structural analysis of the equipment was carried out through a finite element method in different applications, as well as its functional design. A modular and large equipment consisted of few components was conceived with capacity to carry out different tests. Load maximum capacity was nearly 50KN in compression and bend and 23KN traction, showing flexibility for different applications in different industry areas.